Increasing the Efficiency of Electrical Load Calculations Using the Gauss-Seidel Method with Fuzzy Logic - Hendriansyah, Hendriansyah; Siswandari, Noertjahjani; Aris, Kiswanto; Muhammad, Sam'an (PTE FTK UIN Ar-Raniry, 2024)
Improving the accuracy of electric load calculations is a significant task in power system analysis, particularly when dealing with fluctuating loads. Despite its simplicity, the Gauss-Seidel method has historically had trouble handling rapidly changing loads. This paper introduces a novel hybrid approach that increases load computation accuracy and efficiency by fusing fuzzy logic with the Gauss-Seidel method. Fuzzy logic is used in this method to forecast load changes based on previous and present data, which makes load adjustments more precise and faster. The results demonstrate how much better this hybrid technique is than the conventional ones, with accuracy rising from 60% to 84% and efficiency rising by 35%. This makes it an excellent choice for contemporary power systems